MODELS OF FINANCIAL MARKET FUNCTIONING - Viktor I. Lebedev; Inna V. Lebedeva (Вестник Северо-Кавказского федерального университета)
The item provides a focus on various processes in the financial sector of economy seen through a multi-sector model. The author proposes a mathematical model for efficient management of macroeconomic systems in case of financial crisis phenomena. There is also a view on various models of financial sector development, as well as various scenarios analyzed regarding bank capital growth and bankruptcy.